1999
DOI: 10.1148/radiology.213.1.r99se30247
|View full text |Cite
|
Sign up to set email alerts
|

Reperfused Myocardial Infarction as Seen with Use of Necrosis-specific versus Standard Extracellular MR Contrast Media in Rats

Abstract: The sizes of hyperenhanced regions displayed by using mesoporphyrin and gadopentetate dimeglumine differed from each other. The difference in size of the hyperenhanced region demarcated by mesoporphyrin and gadopentetate dimeglumine may provide an estimation of potentially salvageable myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
1
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 36 publications
5
96
1
1
Order By: Relevance
“…In contrast to a previous report, 14 the present study used moderate myocardial injury to create a sizable peri-infarction zone. Multiphase spin-echo MR imaging was used to characterize regional wall thickening.…”
Section: Characterization Of Ischemically Injured Myocardiummentioning
confidence: 88%
See 4 more Smart Citations
“…In contrast to a previous report, 14 the present study used moderate myocardial injury to create a sizable peri-infarction zone. Multiphase spin-echo MR imaging was used to characterize regional wall thickening.…”
Section: Characterization Of Ischemically Injured Myocardiummentioning
confidence: 88%
“…Overestimation of the infarct size by Gd-DTPA confirms previously published data in occlusive and reperfused infarctions. [12][13][14] The difference in the enhanced regions demarcated by the agents may represent the periinfarction zone. Functional MR imaging confirmed that the outer rim of the Gd-DTPA-enhanced zone (peri-infarction zone) is hypokinetic rather than akinetic, whereas the mesoporphyrin-enhanced region is entirely akinetic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations